PENYULUHAN DAN PENCEGAHAN NARKOTIKA, PSIKOTROPIKA DAN ZAT ADIKTIF (NAPZA) BAGI PELAJAR SMP NEGERI 10 KENDARI - Pascayantri, Asniar; Nuralifah, Nuralifah; Jabbar, Asriullah; Dinata, Ade Sundari; Sari, Anita Puspita; Halim, Hikma Lestari; Hajar, Siti; Dewi, Pahtma Purnama Sari (BESIRU : Jurnal Pengabdian Masyarakat, 2025)
The abuse of Narcotics, Psychotropics, and Addictive Substances (NAPZA) has become a serious issue among adolescents, including junior high school students. A lack of understanding and low awareness of the dangers of NAPZA can increase the risk of misuse at an early age. This community service activity aimed to enhance the knowledge and awareness of students at SMP Negeri 10 Kendari regarding the dangers of NAPZA and strategies for its prevention. The method used was an educational intervention through interactive counseling sessions, including discussions and the distribution of educational materials. Evaluation results showed an improvement in students' understanding of the types of NAPZA, the consequences of misuse, and prevention efforts. This activity demonstrates that appropriate and communicative education can serve as an effective preventive measure to reduce the potential for NAPZA abuse among students.